x+2(x-6)=-4(x-1)

Simple and best practice solution for x+2(x-6)=-4(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+2(x-6)=-4(x-1) equation:


Simplifying
x + 2(x + -6) = -4(x + -1)

Reorder the terms:
x + 2(-6 + x) = -4(x + -1)
x + (-6 * 2 + x * 2) = -4(x + -1)
x + (-12 + 2x) = -4(x + -1)

Reorder the terms:
-12 + x + 2x = -4(x + -1)

Combine like terms: x + 2x = 3x
-12 + 3x = -4(x + -1)

Reorder the terms:
-12 + 3x = -4(-1 + x)
-12 + 3x = (-1 * -4 + x * -4)
-12 + 3x = (4 + -4x)

Solving
-12 + 3x = 4 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-12 + 3x + 4x = 4 + -4x + 4x

Combine like terms: 3x + 4x = 7x
-12 + 7x = 4 + -4x + 4x

Combine like terms: -4x + 4x = 0
-12 + 7x = 4 + 0
-12 + 7x = 4

Add '12' to each side of the equation.
-12 + 12 + 7x = 4 + 12

Combine like terms: -12 + 12 = 0
0 + 7x = 4 + 12
7x = 4 + 12

Combine like terms: 4 + 12 = 16
7x = 16

Divide each side by '7'.
x = 2.285714286

Simplifying
x = 2.285714286

See similar equations:

| 13x+2=11-5 | | 3(y-8)-4=-5(-4y+2)-y | | -10=3m | | x*x*x-3*x*x-3*x-1=0 | | -x/6=3/9 | | -x-12+5x=9-10x+7 | | X+(140-g)+(20+g)+g=290 | | N/-10=3 | | 7u+47=3(u+9) | | X/3=1.8 | | 9-7=8 | | 3x-2(x-5)=7x-4(2x+1) | | 35x-5=x+17 | | -x/6=6/9 | | 5(w-2)-7w=-30 | | x^2-8x+13=-4 | | 2x^7+18x^6+36x^5=0 | | X+22=35x | | 18+19m+m^2=0 | | 1/0*190340 | | -3/8=x/24 | | r^2-6r-83=-10 | | -3n+12-n=40+8 | | 7/10-7=7 | | X/10=7/10 | | v^2-12v+34=-6 | | 2+6x-2x=-8+2x | | A^4-2a^2-35=0 | | 2x+3=3x+-2 | | 81r^2-49= | | 17=kg-2 | | 9x^2+8= |

Equations solver categories